2006
DOI: 10.1007/s10278-005-8733-1
|View full text |Cite
|
Sign up to set email alerts
|

Digital Repeat Analysis; Setup and Operation

Abstract: Since the emergence of digital imaging, there have been questions about the necessity of continuing reject analysis programs in imaging departments to evaluate performance and quality. As a marketing strategy, most suppliers of digital technology focus on the supremacy of the technology and its ability to reduce the number of repeats, resulting in less radiation doses given to patients and increased productivity in the department. On the other hand, quality assurance radiographers and radiologists believe that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
62
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 6 publications
(5 reference statements)
5
62
1
2
Order By: Relevance
“…1 This problem has been further compounded by the lack of the software infrastructure necessary to centrally compile data for radiology departments that have multiple digital-capture devices. 2 Quality assurance (QA) tools such as digital dashboards and device clustering software platforms are now available from some manufacturers (Carestream Health at http://www. carestreamhealth.com/).…”
Section: Introductionmentioning
confidence: 99%
“…1 This problem has been further compounded by the lack of the software infrastructure necessary to centrally compile data for radiology departments that have multiple digital-capture devices. 2 Quality assurance (QA) tools such as digital dashboards and device clustering software platforms are now available from some manufacturers (Carestream Health at http://www. carestreamhealth.com/).…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of such process is low, and the continued implementation of quality assurance creates a large burden to the limited human resources of a radiology department. Although automated methods [5,9,13] have been developed for the collection and analysis of repeat images, this type of analysis is influenced by several factors including radiologic technologists' performance and radiographic capabilities. Furthermore, radiologic technologists may be compelled to collect the information involuntarily, which negatively influences the accuracy of information [9].…”
mentioning
confidence: 99%
“…Although automated methods [5,9,13] have been developed for the collection and analysis of repeat images, this type of analysis is influenced by several factors including radiologic technologists' performance and radiographic capabilities. Furthermore, radiologic technologists may be compelled to collect the information involuntarily, which negatively influences the accuracy of information [9]. Past studies have also revealed that the implementation of such data collection methods for quality assurance is not easy, even in a digitized environment [5,14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8] There are several peer-reviewed articles addressing the question or need for a form of higher level quality assessment in the digital Xray department, but none is offering a software solution or a simple means of supporting managers and those responsible for overseeing the quality of digital X-ray imaging in becoming more effective and efficient in delivering the intended service. [9][10][11][12][13] At the beginning of digital projection radiography, repeats, dose, and usage were only manageable by manually scribing ledgers or by printing to film and keeping every exposure as in the traditional workflow fashion. Both methods sacrificed workflow at the department level to enable digital radiographic imaging.…”
mentioning
confidence: 99%